Maturational phase of hippocampal neurogenesis and cognitive flexibility. (15th October 2019) - Webler, Ryan D.; Fulton, Sasha; Perera, Tarique D.; Coplan, Jeremy D.
Highlights: Number of immature new DG neurons predicts CA3 activity during a cognitive flexibility task. Higher number of immature new DG neurons and lower CA3 activity are associated with increased cognitive flexibility. Immature new DG neurons may stifle the retrieval of closely related engrams instantiated in CA3. Abstract: Introduction: Pattern separation aids cognitive flexibility by reducing interference between closely related memories. Dentate gyrus (DG) neurogenesis may facilitate pattern separation by blocking memory retrieval via inhibition of non-neurogenic downstream CA3 neurons. We hypothesized that immature adult-born DG neurons would be associated with decreased CA3 activation and increased cognitive flexibility. Method: Two groups of adult male rats were tested either on the place avoidance task (PAT) (unflipped condition) or a subtly altered-PAT (flipped condition). Four weeks prior, the rats were injected with the mitotic marker BrdU. Immature new neurons were detected by the microtubule protein doublecortin (DCX). Cells that took up BrdU and expressed NeuN were identified as relatively more mature neurons. Synaptic activation was determined by c-Fos expression. Adaptation to the flipped versus unflipped condition reflected a measure of cognitive flexibility. Results: CA3 but not DG c-Fos was lower in the flipped versus unflipped condition [p = 0.002]. CA3 c-Fos correlated inversely with flipped task performance and immature (DCX) neurons with primary and secondary but not tertiary dendrites or more mature (BrdU + NeuN) new neurons. CA3 c-Fos was a significant predictor for the flipped versus unflipped condition specifically for DCX versus BrdU-NeuN neurons. Conclusion: Immature new neurons (DCX+) without tertiary dendrites may be preferentially implicated in cognitive flexibility relative to more mature new neurons (BrdU-NeuN). In combination with decreased CA3 activation in the flipped PAT, the functional contribution of these immature DG neurons may involve the inhibition of postsynaptic CA3 neurons containing traces of previously salient conditioned memories.